2008
DOI: 10.3892/or.19.3.669
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DLC-1 gene expression by RNA interference in the colon cancer LoVo cell line

Abstract: DLC-1 (deleted in liver cancer-1) is a potential tumor suppressor gene, which is inactive in liver carcinogenesis. To observe the effects of DLC-1 gene expression on cell proliferation and migration in the human colon cancer cell line, RNAi Lipo-recombinant of the DLC-1 gene (pGCsil-DLC-1) was constructed and transduced into LoVo cells which are positive for DLC-1 gene expression. Results showed that the RNAi recombinant effectively inhibited the expression of the DLC-1 gene in LoVo cells. Additionally, our da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Overall, ectopic expression of DLC1 suppresses breast, liver, and kidney cancer cell migration (6-8). Meanwhile, silencing of endogenous DLC1 in breast and colon cancer cells promotes migration (9-10). The regulatory mechanism of DLC1 in cell migration as well as other cellular events has been linked to its negative regulation of the RhoA pathway through the GAP domain.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, ectopic expression of DLC1 suppresses breast, liver, and kidney cancer cell migration (6-8). Meanwhile, silencing of endogenous DLC1 in breast and colon cancer cells promotes migration (9-10). The regulatory mechanism of DLC1 in cell migration as well as other cellular events has been linked to its negative regulation of the RhoA pathway through the GAP domain.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has showed that restoration of DLC1 expression in colon cancer HT29 cells significantly inhibited cell proliferation and migration, induced apoptosis and cell cycle arrest [6]. In contrast, inhibition of DLC1 gene expression by RNA interference in LoVo cell line caused adverse effects [7].…”
mentioning
confidence: 99%
“…Reexpression of DLC-1 gene in DLC-1 null cells inhibits tumor cell growth and metastasis (Goodison et al, 2005;Kim et al, 2007). Inhibition of DLC-1 expression using RNA interference promoted cell proliferation and migration of in the colon cancer cell line (Jin et al, 2008) and hepatocellular carcinoma in mice (Xue et al, 2008). These results imply that DLC-1 acts as tumor suppressor gene and may be a candidate therapeutic target for cancer.…”
Section: Discussionmentioning
confidence: 75%